(3OjhGf GHf GdeYJRs - (3CHh GdYHGS YHO Gddg Hf GdeYJR HGddgs; (3GdeTO , Ydj Hf YeQ Hf bRd GdJQceGfj GdjGQhbj, Sja GdOjf,J (B656 (3g` s
(3ChdgG (B:s
(3bGajI GdCda ef GdaNQ hSGQjI dGJed GdHcG LQi OeYgG ai NOhO GdKQi s
(3BNQgG (B:s
(3bGajI GdjGA ai GdRgO GdGjG faS Ef JQVi HbhJ aCfJ ZQjRI GHGZfjI hYi Yfc GdeWGeY hGdCeGfi ece Cefjg ZdHJ efjI s
(3HgG fXGe GdJYbjHIs
(3hgh eQJH Ydi GdCZQGVs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B131s
Keywords: (3GdCOHs